The Application of Multimedia Based Zello Walkie Talkie in Improving First Grade Students’ Speaking Skill at SMK Kesehatan Medika Farma - Fahrur Roji; Dihliza Basya; Fatih Al - Fauzi (FKIP Universitas Islam Jember, 2018)
The objective of this research is to develop the application of multimedia based Zello Walkie Talkie as strategy to improve students’ speaking ability of first grade A students of SMK Kesehatan Medika Farma . The research design used is action research. The data of the study are in the forms of qualitative and quantitative data. The qualitative data were obtained by observing the teaching and learning process and interviewing the students of class XA. The procedures of the research were done through planning, acting, observing and reflecting. Based on the qualitative data, applying Zello Walkie Talkie media gave the students more chances to speak in English. These findings were also supported by the result of the students’ speaking scores. The mean improved to 79.6. It indicates that they made a considerable improvement in some aspects of speaking skills such as pronunciation, fluency, grammar, and vocabulary. Keywords: zello walkie talkie, speaking ability